Pregnancy-associated plasma protein-A, progesterone, and oestriol levels and some birth outcomes in HIV-seropositive pregnant women at Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria - John Ekenedirichukwu Okwara; Joseph Eberendu Ahaneku; Charles Chinedum Onyenekwe; Gerald Okanandu Udigwe; Joseph Ifeanyichukwu Ikechebelu; Emmanuel Chidiebere Okwara; Nuratu Adejumoke Okwara; Jude Anaelechi Onuegbu; Japhet Madu Olisekodiaka (Nigerian Journal of Medicine, 2023)
Background: Pregnancy is associated with biochemical alterations and may be compounded by human immunodeficiency virus (HIV) infection potentially affecting pregnancy outcome such as birth weight, Apgar score, and foetal viability (stillbirth or intrauterine foetal death [IUFD]). Aims: This prospective case–control study evaluated some biochemical parameters and their possible effects on pregnancy outcome in HIV-seropositive subjects. Patients, Materials and Methods: The study involved 136 HIV seropositives on highly active antiretroviral therapy and 137 HIV-seronegative pregnant women, recruited from the Antenatal Clinic of Nnamdi Azikiwe University Teaching Hospital, Nnewi. Pregnancy-associated plasma protein-A (PAPP-A), oestriol (E3), and progesterone were analysed using an enzyme-linked immunosorbent assay method, and the delivery outcomes were reported. Results: Progesterone was significantly higher (P = 0.002) in HIV-seropositive individuals (59.3 ± 17.84 ng/mL) compared to controls (54.89 ± 8.24 ng/mL). There were no significant differences in the levels of E3 and PAPP-A between the two groups. In HIV seronegatives, there were no significant changes in measured biochemical parameters between trimesters (P > 0.05). There were no significant differences in measured biochemical parameters between subjects with IUFD and subjects with live births (P > 0.05) for both the test and control groups. Subjects with significantly lower PAPP-A in HIV seropositives had babies with higher Apgar score. The incidence of IUFD was 7.31% among HIV seropositives and 7.47% among HIV seronegatives. Conclusion: HIV infection affects some biochemical indices such as progesterone and PAPP-A but does not adversely affect pregnancy outcomes in HIV seropositives under antiretroviral therapy.